New Perspective of Life Style Drugs - Dimri, Mayank; Rajwar, Virbal Singh; Kush, Luv; Maithani, Alok (Asian Journal of Pharmaceutical Research and Development, 2020)
The life style drugs have opened a new therapeutical horizon in pharmaceutical scenario. They have booming market and became multi-million dollar international industry. The new categories of drugs – anti-obesity, anti-dementia and anti-phobial are included in them. Nootropics are novel life style products for males.